Uji Daya Hambat Ekstrak Etanol Kubis (Brassica oleracea var. capitata f. alba) Terhadap Bakteri Staphylococcus aureus Secara In Vitro - Siti Fatimah; Fitri Nadifah; Islami Burhanudin (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Infectious diseases are diseases caused by pathogenic bacteria that enter the body, multiply and cause disease. One cause of the disease is a bacterial infection of Staphylococcus aureus. Treatment of infectious diseases is usually done by giving antibiotic but some types of bacteria become resistant. Utilization of plants as traditional medicine is growing rapidly and many alternative medicine used by some communities, one of which is cabbage (Brasicca oleracea var. capitata f. alba) containing antibacterial compounds such as flavonoids, saponins, polyphenols, tannins and sulfur. Such compounds capable of inhibiting the growth of bacteria by inhibiting bacterial cell wall synthesis, protein synthesis, and forming complex compounds against extracellular proteins that interfere with bacterial cell membrane integrity. This research is an experimental research with the aim to determine the inhibitory ethanol extract of cabbage (Brasicca oleracea var. capitata f. alba) against Staphylococcus aureus in in vitro. Antibacterial test method used is that pitting diffusion method. Ethanol extract of cabbage (Brasicca oleracea var. capitata f. alba) can inhibit the growth of Staphylococcus aureus on the mark with the formation of a clear zone around the wells which starts from a concentration of 20%.